A Review of Pulmonary Arterial Hypertension Treatment in Extracorporeal Membrane Oxygenation: A Case Series of Adult Patients - Heather Torbic PharmD, BCPS, BCCCP; Benjamin Hohlfelder PharmD, BCPS, BCCCP; Sudhir Krishnan MD; Adriano R. Tonelli MD, MSc (SAGE Publishing, 2022)
Background: Little data is published describing the use of medications prescribed for pulmonary arterial hypertension (PAH) in patients receiving extracorporeal membrane oxygenation (ECMO). Even though many patients with PAH may require ECMO as a bridge to transplant or recovery, little is reported regarding the use of PAH medications in this setting. Methods: This retrospective case series summarizes the clinical experience of 8 patients with PAH receiving ECMO and reviews medication management in the setting of ECMO. Results: Eight PAH patients, 5 of whom were female, ranging in age from 21 to 61 years old, were initiated on ECMO. Veno-arterial (VA) ECMO was used in 4 patients, veno-venous (VV) ECMO and hybrid ECMO configurations in 2 patients respectively. Common indications for ECMO included cardiogenic shock, bridge to transplant, and cardiac arrest. All patients were on intravenous (IV) prostacyclin therapy at baseline. Refractory hypotension was noted in 7 patients of whom 5 patients required downtitration or discontinuation of baseline PAH therapies. Three patients had continuous inhaled epoprostenol added during their time on ECMO. In patients who were decannulated from ECMO, PAH therapies were typically resumed or titrated back to baseline dosages. One patient required no adjustment in PAH therapy while on ECMO. Two patients were not able to be decannulated from ECMO. Conclusion: The treatment of critically ill PAH patients is challenging given a variety of factors that could affect PAH drug concentrations. In particular, PAH patients on prostacyclin analogues placed on VA ECMO appear to have pronounced systemic vasodilation requiring vasopressors which is alleviated by temporarily reducing the intravenous prostacyclin dose. Patients should be closely monitored for potential need for rapid titrations in prostacyclin therapy to maintain hemodynamic stability.